Application of Multi Attributes for Feasibility Study of Fractures and Structural Anomalies in Malaysian Basin - Hamidi, Rosita; Bashir, Yasir; Prasad Ghosh, Deva; Akhtar, Saeed; Iqbal Sheikh, Manan (International Journal of Engineering and Technology, 2018)
There have been lots of efforts to study the geological characteristics and structure of the Malaysian Basin. Faults and fractures are of great importance due to the role they can play affecting different phases of a hydrocarbon prospect life from exploration through production and even abandonment. Carbonate build-ups are another type of significant geological anomalies in the area; because they are proved to be promising prospects. Application of seismic attributes on three dimensional seismic data has been proved to be useful in the study of such features. Each attribute is based on certain property of the seismic data which itself is the result of relevant geological phenomena. In this paper, different seismic attributes that can emphasize on the aforementioned geological anomalies are used in Malaysian Basin. Based on the results and their comparison, it is seen that combination of the results of different attributes can provide a much more convenient outcome.Â Â